Racial Politics and Sexual Violence in Post-Apartheid Contemporary South Africa in John Maxwell Coetzee’s Disgrace (2000) - Babacar Diakhaté (Britain International for Academic Research (BIAR) Publisher, 2019)
The abolition of apartheid does not necessarily mean the resolution of social, political, racial and ethnic questions prevailing in South Africa. In Disgrace (2000), John Maxwell Coetzee depicts racial politics and gender, Sexism, social marginalization and alienation in South Africa. The aim of this article is to pinpoint sexual harassment and black females’ abuse by the whites in Post-Apartheid South Africa. It shows whether sexual violence such as rape happens more in black South Africa than in the white community.